Fundamentals of philosophy - Shand, John (Routledge, 2003)
Fundamentals of Philosophy is a comprehensive and accessible introduction to philosophy. Based on the well-known series of the same name, this textbook brings together specially commissioned articles by leading philosophers of philosophy's key topics. Each chapter provides an authoritative overview of topics commonly taught at undergraduate level, focusing on the major issues that typically arise when studying the subject. Discussions are up to date and written in an engaging manner so as to provide students with the core building blocks of their degree course. Fundamentals of Philosophy is an ideal starting point for those coming to philosophy for the first time and will be a useful complement to the primary texts studied at undergraduate level. Ideally suited to novice philosophy students, it will also be of interest to those in related subjects across the humanities and social sciences.